Autoimmune liver serology before and after successful treatment of chronic hepatitis C by direct acting antiviral agents. (August 2019) - Terziroli Beretta-Piccoli, Benedetta; Di Bartolomeo, Claudia; Deleonardi, Gaia; Grondona, Ana Gabriela; Silvestri, Tania; Tesei, Cinzia; Melidona, Laura; Cerny, Andreas; Mertens, Joachim; Semmo, Nasser; Semela, David; Moradpour, Darius; et al.
Abstract: Background and aims: Chronic hepatitis C virus (HCV) infection is associated with a wide range of immunopathological manifestations, which are significantly improved by successful interferon-based treatment. There is paucity of data on the impact of interferon-free HCV clearance on immunopathological manifestations, which might be expected to disappear more frequently as compared to what reported in interferon-induced HCV-clearance. We have investigated liver autoimmune serology before and after interferon-free clearance of HCV by treatment with direct acting antiviral agents (DAA). Method: Patients within the Swiss Hepatitis C Cohort Study who underwent successful (SVR 12) HCV treatment with DAA were tested for autoimmune liver serology according to dedicated guidelines before and at least 6 months after end of treatment. Results: A total of 235 patients were included; 62% males; median age 56 years; 27% with cirrhosis. Median time between end of DAA treatment and post-treatment serum sampling was 17 months. At least one autoantibody before treatment was found in 175 (74%) patients ; 32 (14%) were positive for 2 autoantibodies; no patient was positive for anti-SLA, anti-LC1 or typical AMA before or after DAA. ANA disappeared in 34%, SMA in 52% and anti-LKM1 in one of two patients after successful treatment, but, unexpectedly, one or more autoantibodies appeared in 27% of pre-treatment negative subjects. Conclusion: HCV clearance by DAA is associated with autoantibody disappearance in more than one third of the patients who were positive before treatment. However, the majority of the patients remain autoantibody-positive and 27% of those who were negative before treatment developed autoantibodies after DAA-induced HCV clearance. These data confirm that HCV infection is associated with autoimmunity and show that the autoimmune imprint persists after viral clearance by DAA, suggesting that long-term follow-up may be warranted. Highlights: Hepatitis C infection (HCV) is associated with liver autoantibodies. Liver autoantibodies were tested in 235 adult patients before and after DAA-induced HCV clearance. Liver autoantibodies disappear in a high proportion of patients after DAA-induced HCV-clearance. However, the majority of patients remain autoantibody-positive. 27% of patients seronegative while viraemic, develop autoantibodies after HCV-clearance.